2021
DOI: 10.1155/2021/6419774
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Stress in Obturator Prostheses: A Systematic Review of Finite Element Studies

Abstract: Aim. This systematic review is aimed at investigating the biomechanical stress that develops in the maxillofacial prostheses (MFP) and supporting structures and methods to optimize it. Design and Methods. A literature survey was conducted for full-text English articles which used FEA to examine the stress developed in conventional and implant-assisted MFPs from January 2010 to December 2020. Results. 87 articles were screened to get an update on the desired information. 74 were excluded based on a complete scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Varying designs of removable partial dentures, involving variances in the shape of the clasp and thickness of the framework, had been shown to possess a significant effect on abutment teeth as well as the surrounding oral soft and hard tissues [ 31 , 32 , 33 , 34 ]. With the goal of clarifying the design principles of PEEK RPDs, the stress distribution of the PEEK RPD framework in different designs will be further improved and analyzed in the subsequent research to find the best design for various cases of dentition defect.…”
Section: Discussionmentioning
confidence: 99%
“…Varying designs of removable partial dentures, involving variances in the shape of the clasp and thickness of the framework, had been shown to possess a significant effect on abutment teeth as well as the surrounding oral soft and hard tissues [ 31 , 32 , 33 , 34 ]. With the goal of clarifying the design principles of PEEK RPDs, the stress distribution of the PEEK RPD framework in different designs will be further improved and analyzed in the subsequent research to find the best design for various cases of dentition defect.…”
Section: Discussionmentioning
confidence: 99%
“…Inan et al (32) compared FEM and photoelastic methods for evaluating stress in the supporting bone around implants and found that both methods provide stress distribution information, but FEM provides more detailed and comprehensive results. Mousa et al (33) analyzed obturator biomechanical stresses using FEM and concluded that FEM can be reliably used to analyze stress distribution in various defect types, prosthesis rehabilitations, and supporting structures. Based on these studies, stress analysis using FEM was conducted in our research.…”
Section: Discussionmentioning
confidence: 99%
“…8 Using Zigomatic Implant in the edentulous maxillary defect was found more advantageous, in terms of compression and tensile stress and retention, when compared with conventional dental Implant. 9 Except when contraindicated due to financial or surgical considerations, implant-assisted overdentures are usually the treatment of choice. During this case, although the patient understands the advantages of implantsupported prosthesis she isn't interested and only prefers a non-invasive conventional treatment.…”
Section: Discussionmentioning
confidence: 99%